Field experience of well testing using multiphase Coriolis metering. (December 2016) - Henry, Manus; Tombs, Michael; Zhou, Feibiao
Abstract: A previously described Net Oil & Gas Skid (Henry et al., 2013) [1] combines a multiphase Coriolis mass flow meter with a water cut meter to generate on-line estimates of oil, water and gas flow rates, with an update rate of one second. This system has received approval from GOST, the Russian standards agency, for use in upstream oil and gas applications. The NOG system has been applied to well testing, where the output of an individual well is measured, typically over several hours. The conventional equipment used for this task is a test separator; however, a separator only provides the totalised flows of oil, water and gas over the test period. By contrast, the NOG system is able to provide time series of each flow rate, thus allowing more detailed characterisations of well behaviour. This paper draws on the results of several hundred well tests carried out in Russia to illustrate the different types of well behaviour observable using the Net Oil & Gas Skid. Highlights: Examples are given of actual well tests monitored using a Net Oil & Gas skid. Detailed time profiles of well behaviour are provided for several wells. Different examples of well behaviour are indicated.